Optimalisasi Budidaya Bawang Merah Melalui Pendampingan Terpadu dan Pengamatan Lapang Di Kabupaten Probolinggo: Optimization of Shallot Cultivation through Integrated Assistance and Field Observation in Probolinggo Regency - Sunarto, Bintar Probo; Taufiqurrahman, Achmad Fitriadi; Abadi, Abdul Latief; Hamdani, Rizky Dwi (AGROINOTEK Jurnal Penelitian dan Pengabdian Masyarakat, 2025)
Improving the productivity of shallots (Allium cepa var. aggregatum) has become one of the main priorities in supporting food security and increasing farmers’ income in Probolinggo Regency, East Java. This study aims to optimize shallot cultivation through an integrated assistance and education approach, as well as the implementation of sustainable agricultural practices. The methods used include Focus Group Discussions (FGD), biological agent training, compost-making training, and field monitoring of practice implementation. The results of the community engagement program indicate that the major challenges faced by farmers are pest and disease attacks, limited access to environmentally friendly cultivation technologies, and the Impacts of climate change. Training on the use of biological agents and organic compost utilization significantly improved farmers’ understanding of pest and disease management and soil health conservation. This assistance program strengthened farmers’ technical capacity in adopting sustainable farming systems and contributed to increased productivity and local economic welfare. These findings highlight the importance of integrating biotechnological innovations and organic-based soil management in the development of sustainable shallot cultivation.